CULTURAL HERITAGE AND TOURISM IN ŞALIURFA MEDIEVAL CAVE STONE QUARRIES “BAZDA CAVES” - ÇETINER ÖZDEMIR, Olcay; TUNÇAY, Fatma; ÖZDEMIR, Şentürk (Studia Universitatis Babeș-Bolyai Negotia, 2022)
Cultural and natural heritage is a consociate heritage of all humanity. As the country and region where the cultural heritage is located gains importance, more tourists come and thus economic gain for the region increases with tourism. Located in the UNESCO World Heritage Tentative List, the Bazda Caves with their appearance and mysterious history, that are located within the borders of the historical Harran district of Şanlıurfa, should be introduced to the world by bringing them together with cultural tourism. In the study, “Bazda Caves” will be examined and the relationship with tourism as a Cultural Heritage value will be conveyed. Article history: Received 18 April 2022; Revised 23 May 2022; Accepted 7 June 2022; Available online 30 June 2022; Available print 30 August 2022. JEL Classification: L83, Z00, Z39